Identification and analysis of power substrates degradations subjected to severe aging tests. Issue 9 (August 2015) - Woirgard, E.; Arabi, F.; Sabbah, W.; Martineau, D.; Theolier, L.; Azzopardi, S.
Abstract: Severe thermal cycles [− 55 °C/+ 245 °C] have highlighted degradations in Active Metal Brazing Si3 N4 power substrates with copper metallization, nickel-plated and gold finish. After 1000 thermal cycles, the metallization patterns of the top side were imprinted on the rear one due to microcracking of the rear surface metallization and the surface roughness modification. This phenomenon was not observed in less severe thermal cycles such as [-40 °C/+ 150 °C]. This study focuses on the causes of this degradation appearance and on issues to prevent such phenomenon. First, the power electronics context is presented to justify the severe stresses applied to high temperature power modules and then induced degradations were described and analyzed. The choice was to perform a protocol of aging process by finite element simulations in order to have a better understanding on the propagation of mechanical stresses in the substrate which is the origin of these degradations. Indeed, this phenomenon could be reproduced by thermomechanical simulations. To propose solutions for these metallization reconstructions, the effect of the copper metallization thickness, the coefficient of thermal expansion of this layer, the substrate warpage and the size of metallization bonding tracks were assessed. The objective is to offer technological choices in terms of geometry of metallization track bonding (minimal etching or traditional engraving) and choices of materials used in power substrates in order to avoid these degradations in extreme environment conditions. Highlights: Severe thermal cycles [-55°C/+245°C] have highlighted degradations in Active Metal Brazing Si3 N4 power substrates. The metallization patterns of the top side were imprinted on the rear one due to microcracking of the rear metallization. This study proposes solutions for these metallization reconstructions. This study has illustrated that the degradation occurred during severe thermal cycles is thermomechanically based. All technological choices which allowed reducing the differential expansion between the materials are relevant.